Linkages Between Incarceration and Health. (May 2019) - Massoglia, Michael; Remster, Brianna
The dramatic expansion of the US penal system during the past 4 decades has led to an increase in adverse health conditions that affect an unprecedented number of individuals. This article first provides an overview of the literature on the immediate and lasting associations between incarceration and physical health, highlighting the diverse health conditions linked with incarceration, including health functioning, infectious disease, chronic conditions, and mortality. Next, we discuss potential explanations for the associations between incarceration and these health conditions, focusing on stress, contagion, social integration, and reintegration challenges. We then consider how medical and social science research can be combined to advance our understanding of these health conditions and suggest ways to reduce the negative association between incarceration and health, such as by improving prison conditions and medical care both inside prisons and after release.